Returns to Education in China: Evidence from the Great Higher Education Expansion - Bin Huang; Massimiliano Tani; Yi Wei; Yu Zhu (Global Labor Organization (GLO), 2022)
China experienced a near 5-fold increase in annual Higher Education (HE) enrolment in the decade starting in 1999. Using the China Household Finance Survey, we show that the Great HE Expansion has exacerbated a large pre-existing urban-rural gap in educational attainment underpinned by the hukou (household registration) system. We instrument the years of schooling with the interaction between urban hukou status during childhood and the timing of the expansion - in essence a difference-in-differences estimator using rural students to control for common time trends. We find that the Great HE raised earnings by 17% for men and 12% for women respectively, allowing for county fixed-effects. These Two Stage Least Squares (2SLS) estimates, which are robust to additional controls for hukou status at birth fully interacted with birth hukou province, can be interpreted as the Local Average Treatment Effect (LATE) of education on earnings for urban students who enrolled in HE only because of the Great HE Expansion. For the selected subsample of respondents with parental education information, we find that the 2SLS returns for students from more disadvantaged backgrounds are at least as high as their more advantaged counterparts, for both genders.
Keywords: I26; I23; 330; returns to education; 2SLS; higher education expansion; China